The Eﬀicacy of Phosphodiesterase-5 Inhibitors on Pulmonary Vascular Resistance in Patients with Single Ventricle Physiology - Rhinza Seputra Simanjuntak; Miftah Pramudyo; Frisky Ronald Tua Marbun; Rheza Felari Simanjuntak; Tatyana Sianipar (The International Journal of Medical Science and Health Research, 2025)
Introduction: Patients with single ventricle physiology often undergo the Fontan procedure, creating a circulation highly dependent on low pulmonary vascular resistance (PVR) for long-term success. Phosphodiesterase-5 (PDE-5) inhibitors are used as targeted pulmonary vasodilators to improve these hemodynamics. This systematic review aims to evaluate the efficacy of PDE-5 inhibitors on PVR and associated clinical outcomes in this specific patient population. Methods: Following the PRISMA 2020 guidelines, a comprehensive search was conducted across multiple databases, including PubMed and Google Scholar, using PICO-based keywords. Eligibility screening of abstracts and full-text articles was performed to include randomized controlled trials and cohort studies. After a rigorous selection process, 34 relevant studies were included in the final qualitative synthesis. Results: The analysis revealed consistent hemodynamic improvements. A significant reduction in PVR or its related indices was explicitly reported in 11 studies , while 20 studies noted a decrease in pulmonary artery pressure. These benefits translated to improved clinical outcomes, with 11 studies demonstrating enhanced exercise capacity and 13 studies reporting increased oxygen saturation. The safety profile was highly favorable, as 25 studies reported no significant adverse events. However, significant statistical heterogeneity was detected among studies (I²=94%). Conclusion: PDE-5 inhibitors are a safe and effective therapy for improving short-term hemodynamics, exercise capacity, and oxygenation in patients with single ventricle physiology. While the evidence strongly supports their use, it is limited by substantial heterogeneity and a lack of long-term data. Large-scale, standardized randomized controlled trials are imperative to establish definitive long-term benefits and formulate optimal clinical guidelines.